2011
DOI: 10.3758/s13414-011-0199-2
|View full text |Cite
|
Sign up to set email alerts
|

Signal detection evidence for limited capacity in visual search

Abstract: The nature of capacity limits (if any) in visual search has been a topic of controversy for decades. In 30 years of work, researchers have attempted to distinguish between two broad classes of visual search models. Attention-limited models have proposed two stages of perceptual processing: an unlimited-capacity preattentive stage, and a limited-capacity selective attention stage. Conversely, noise-limited models have proposed a single, unlimited-capacity perceptual processing stage, with decision processes inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 41 publications
1
43
0
Order By: Relevance
“…We have typically failed to find efficient search for consistently mapped character sets even when this is as simple as a search for “T”s among “L”s (e.g. Palmer, Fencsik, Flusberg, Horowitz, & Wolfe, 2011). The topic deserves more research.…”
Section: Resultsmentioning
confidence: 99%
“…We have typically failed to find efficient search for consistently mapped character sets even when this is as simple as a search for “T”s among “L”s (e.g. Palmer, Fencsik, Flusberg, Horowitz, & Wolfe, 2011). The topic deserves more research.…”
Section: Resultsmentioning
confidence: 99%
“…In essence, top-down guidance works in two ways: it biases attention toward important features or regions, and it biases attention away from undesirable features (or objects that have already been inspected; Al-Aidroos et al, 2012; Arita, Carlisle, & Woodman 2012). It is unsurprising that successful models of visual search, such as Guided Search (Wolfe et al, 1989; Wolfe, 1994; Wolfe & Gancarz, 1996, Wolfe, 2007; Palmer et al, 2011), incorporate top-down guidance as a key mechanism controlling attention.…”
Section: Guidance Of Attention By Bottom-up and Top-down Informationmentioning
confidence: 99%
“…Visual search studies have also suggested sometimes that visual attention operates to select and integrate visual features supplied by Bpre-attentive^vision (e.g., E. Palmer et al, 2011;Treisman & Gelade, 1980;Wolfe et al, 1989). Pre-attentive vision is sometimes conceived as an unlimited capacity parallel process.…”
Section: Empirical Observationsmentioning
confidence: 99%